Implementation of Al-Qur'an Integration in the Teaching and Learning Process - Sukamad, Sukamad; Sulistiyo, Urip; Yanto, Yanto (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
In the Qur'an, knowledge is seen as something special that makes humans superior to other creatures. The importance of instilling religious and spiritual values ​​in general learning is to increase faith and piety to God Almighty in respecting the universe. The research aims to see how the integration of the Qur'an is implemented in the teaching and learning process, in which the Qur'an is science based on revelation, the hadith of the prophet, and the ijtihad of the scholars, while general science is based on human reasoning based on empirical data, through research. This research uses a qualitative descriptive approach with a phenomenological research type. In this study, the sampling technique used was snowball and purposive. The procedures and techniques used in collecting data in this study are qualitative: observation, FGD, and documentation. The stages of this study presented three stages, namely 1) the pre-field stage, 2) the fieldwork stage, and 3) the data analysis stage. The result of the research is that integrating the Al-Qur'an in the teaching and learning process can be applied well, with efforts to provide training related to the integration of the Al-Qur'an. Implementing Al-Qur'an integration is carried out by internalizing Al-Qur'an values ​​through studies in learning that can be carried out with curriculum integration, learning integration, and integration of Islamization of science.